Development and Feasibility of a Culturally Sensitive Cooking and Physical Activity Program Designed for Obese Hispanic Families. (April 2015) - Li, Rhea; Raber, Margaret; Mejia, Luz; Domenech, Marite; Brewster, Anna; Swartz, Maria C.; Strong, Larkin; Chandra, Joya
Objective : To determine whether a 10-week cooking and physical activity pilot intervention could be delivered in a health care setting. Development and feasibility of the program with a small sample size are explored. Methods : The MUNDO (Moviéndonos hacia Una Nutrición Divertida y Óptima) program was delivered weekly at a local primary care clinic. The curriculum included culturally sensitive cooking demonstrations, tastings, and organized physical activity sessions for children and their parents. Questionnaires and measurements were completed at baseline and completion of the study. Outcomes were feasibility, anthropometrics, and behavior change. Results : Four families were recruited, and 3 families attended 74% of the sessions. No significant changes in outcomes were reported. Families provided positive feedback about most aspects of the program. Conclusions : Future research is needed to understand how delivery of MUNDO could be optimized, within and beyond a clinic setting. Low-cost meal planning and cultural sensitivity of this program are unique features of MUNDO, which suggest that a larger trial with a greater number of participants and more rigorous recruitment would be warranted.